Conditions for implementation of logistics into companies of chemical industry in Czech Republic - Vlčková, Vladimíra (Univerzita Pardubice, 2004)
Status quo in implementation of logistics into companies of chemical industry in the Czech Republic is presented. The reasons that inhibit quicker assertion of logistics into these companies are discussed. Recommendations for a successful implementation of logistic system are given. Unfinished privatization and the therewith related frequent changes in ownership on this branch of industry was identified as the most significant problem.